Digital Aset Management Sebagai Strategi Keberlangsungan Museum Prabu Geusan Ulun di Era Keterbukaan Informasi Publik - Wicaksono, Bintarto; Sunarmi, Sunarmi (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2024)
Prabu Gesaun Ulun Museum is currently an institution that preserves the culture and heritage of the kingdom of Sumedang, West Java. To improve information services to the public through technological developments, in this case the Prabu Gesaun Ulun Museum will improve museum media so that people can easily get complete information. The design stage of social media management focuses on archiving all the relics of the Sumedang Kingdom in the form of objects and other arts and activities. With the concept of Digtal Asset Management or DAM, it can provide solutions that can follow the needs of the digital era. Currently available is the website museumprabugeusanulun.org, with content that is still very simple and only some archiving of objects in the museum. Further development is needed in terms of information media and digital archives about all kinds of collections in the museum, both in the form of objects and stories from trusted sources. In terms of information media, it is also very necessary to develop through social media to provide information on all kinds of activities, and other information related to the development of the Prabu Gesaun Ulun Museum as part of the history of civilization in West Java, especially Sunda. Furthermore, it is hoped that Prabu Gesaun Ulun Museum can become part of a new destination both directly and virtually through the media. This is expected to provide support for the sustainability of the Museum and the continuity of the history of Sundanese civilization.